Carbon Storage of Leyte Sab-A Basin Peatland, Philippines: 10.32526/ennrj/21/20230015 - Bobon-Carnice, Pearl Aphrodite; Chanton, Jeffrey P.; Migo, Veronica P.; Faustino-Eslava, Decibel V. (Environment and Natural Resources Journal, 2023)
Leyte Sab-A Basin peatland (LSBP) is the second largest peatland in the Philippines and comprises 3,088 ha (31 km2). The study estimated the C storage and carbon sequestration capacity of the peatland’s four (4) ecotypes, namely, swamp forest (SF), marshland (ML), agroforestry (AF), and agricultural land (AL) using allometric equations. SF rendered the highest downed wood C-stocks followed by AL and AF. For the litter C-stocks, AF rendered the highest, followed by SF, ML, and AL. SF rendered the highest root C-stocks and CO2 sequestered, followed by AL and AF. C% is highest in ML with values ranging from 32-43 C% across the soil peat depth, while SF ranges from 29-34 C%, and AL and AF both with 19-37 C%. The LSBP stores 36.6 Tg of C and 134.5 Tg of CO2 sequestered. This C storage amount can represent 0.04% of tropical peat carbon.